2018
DOI: 10.1016/j.cogdev.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Short-and long-term memory determinants of novel word form learning

Abstract: This work was supported by a grant from Fonds de la Recherche Scientifique -F. R. S. -FNRS (PDR, FRFC, T.1003.15, Belgium). The authors thank Marie Gomrée for her help in the data collection and all the school directors, teachers, pupils, and parents for their time and collaboration. We are also grateful to Eleonore Smalle and Lize Van der Linden for helping us with the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 68 publications
4
29
0
Order By: Relevance
“…Similar effects have been found using lexical learning paradigms (Majerus, Poncelet, et al, 2008;Ordonez Magro, Attout, Majerus, & Szmalec, 2018;Storkel et al, 2006).…”
Section: Introductionsupporting
confidence: 80%
“…Similar effects have been found using lexical learning paradigms (Majerus, Poncelet, et al, 2008;Ordonez Magro, Attout, Majerus, & Szmalec, 2018;Storkel et al, 2006).…”
Section: Introductionsupporting
confidence: 80%
“…At the behavioral level, it has been shown that the distinction between item and order verbal WM processes is crucial for understanding the links between verbal WM abilities and cognitive development in various domains (Attout, Noël, & Majerus, ; Leclercq & Majerus, ; Martinez Perez, Majerus, & Poncelet, ; Ordonez Magro, Attout, Majerus, & Szmalec, ). Several previous behavioral and neuropsychological studies in adults already supported this dissociation between item and order verbal WM by showing for example selective influence of psycholinguistic variables on each process and specific deficits in brain damaged patients or patients with semantic dementia (Attout, Van der Kaa, George, & Majerus, ; Majerus, Norris, & Patterson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific alterations in serial order WM abilities, as opposed to item WM abilities, have been observed in genetic syndromes such as 22q11.2 microdeletion syndrome or Down syndrome (Brock & Jarrold, ; Majerus, Glaser, Van der Linden, & Eliez, ; Majerus, Van der Linden, Braissand, & Eliez, ) as well as in learning disorders such as dyslexia or dyscalculia (Attout & Majerus, ; De Visscher, Szmalec, Van Der Linden, & Noël, ; Martinez Perez, Majerus, Mahot, & Poncelet, ), and this for both verbal and visuospatial material. Developmental studies have also shown that estimates of serial order WM capacity (in the verbal modality) are particularly robust predictors of lexical, reading, spelling, and calculation abilities, as compared to estimates of item WM (Attout et al, ; Binamé & Poncelet, ; Leclercq & Majerus, ; Majerus & Boukebza, ; Majerus, Poncelet, Greffe, & Van der Linden, ; Martinez Perez, Majerus, & Poncelet, ; Ordonez Magro et al, ). These studies highlight the importance of distinguishing between item and serial order WM processes, both in order to understand the nature of WM impairment in specific neurodevelopmental populations as well as in order to understand the functional role of WM abilities in cognitive development.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies with both children and adults have found strong associations between performance on verbal immediate serial-recall tasks (e.g., digit span tasks) and vocabulary acquisition. This suggests that verbal short-term memory, and in particular short-term memory for serial-order information, not item information (Majerus & Boukebza, 2013;Ordonez-Magro, Attout, Szmalec & Majerus, 2018;Romani, Tsouknida, & Olson, 2015), supports lexical development (Gathercole, Service, Hitch, Adams, & Martin, 1999;Gathercole, 2006;Gupta, 2003;Page & Norris, 2009). More directly, Szmalec and colleagues found that repetitive immediate serial recall of syllable sequences creates long-term representations of novel word-forms in the mental lexicon (Szmalec, Duyck, Vandierendonck, Mata, & Page, 2009;Szmalec, Page, & Duyck, 2012).…”
mentioning
confidence: 99%